Short stature and delayed puberty in gymnasts: influence of selection bias on leg length and the duration of training on trunk length - Bass, S.; Bradney, M.; Pearce, G.; Hendrich, E.; Inge, K.; Stuckey, S.; Lo, S. K.; Seeman, E. (The Journal of Pediatrics, 2000)
BACKGROUND: Delays in bone age, the onset of puberty, and skeletal growth in gymnasts could be, in part, the reason for an interest in gymnastics, rather than being the result of vigorous exercise. We hypothesized that short stature and delayed bone age are present at the start of gymnastics, and training delays growth, producing short stature, even after retirement. METHODS: Sitting height and leg length were measured in 83 active female gymnasts, 42 retired gymnasts, and 154 healthy control subjects. Results were expressed as age-specific SD scores (mean +/- SEM). RESULTS: In the cross-sectional data, active gymnasts had delayed bone age (1.3 +/- 0.1 years), reduced height -1.32 +/- 0.08 SD, sitting height -1.24 +/- 0.09 SD, and leg length, -1.25 +/- 0.08 SD (all P <.001). However, in those training for less than 2 years, the deficit was confined to leg length (-0.8 +/- 0.2 SD).During 2 years of follow-up of 21 gymnasts, only the deficit in sitting height worsened (by 0.4 +/- 0.1 SD). In 13 gymnasts followed up in the immediate 12 months after retirement, sitting height accelerated, resulting in a lessening of the deficit in sitting height by 0.46 +/- 0.14 SD (P <.01). Adult gymnasts who had been retired for 8 years had no deficit in sitting height, leg length, or menstrual dysfunction. CONCLUSIONS: Short stature in active gymnasts is partly due to selection of individuals with reduced leg length. Reduced sitting height is likely to be acquired but is reversible with cessation of gymnastics. A history of gymnastic training does not appear to result in reduced stature or menstrual dysfunction in adulthood.